PERAN LAYANAN KONSELING BAGI PERSONIL KEPOLISIAN SEBAGAI UPAYA MENGATASI PERMASALAHAN BEKERJA - Aurora; Putri Bulqis; Nadia Cantika1; Laila Syaharani; Marselina Susanti; Affan Yusra (BULLET : Jurnal Multidisiplin Ilmu, 2022)
With the increase in cases and problems that must be handled by police personnel, it is often a driver of stress and problems that hinder the optimization of their assignments. The design used is a literature review where journal references are collected using the Google search engine and Google Scholar. By setting the criteria, the journals used are those published in 2017-2022, and e-books published in 2012-2022. Based on the journals collected, the results obtained are that there is still very little provision of counseling services to police personnel, but there have been various variations of counseling service models that can be provided to police personnel. It is hoped that the counseling services provided by the counselor will be able to become a media solution in alleviating individual problems that are owned by each police officer and improve the quality of their work.